Computation-Driven Analysis of Model Polyextremo-tolerant Fungus Exophiala dermatitidis: Defensive Pigment Metabolic Costs and Human Applications - Schroeder, Wheaton L.; Harris, Steven D.; Saha, Rajib (iScience, 2020)
The polyextremotolerant black yeast Exophiala dermatitidis is a tractable model system for investigation of adaptations that support growth under extreme conditions. Foremost among these adaptations are melanogenesis and carotenogenesis. A particularly important question is their metabolic production cost. However, investigation of this issue has been hindered by a relatively poor systems-level understanding of E. dermatitidis metabolism. To address this challenge, a genome-scale model (iEde2091) was developed. Using iEde2091, carotenoids were found to be more expensive to produce than melanins. Given their overlapping protective functions, this suggests that carotenoids have an underexplored yet important role in photo-protection. Furthermore, multiple defensive pigments with overlapping functions might allow E. dermatitidis to minimize cost. Because iEde2091 revealed that E. dermatitidis synthesizes the same melanins as humans and the active sites of the key tyrosinase enzyme are highly conserved this model may enable a broader understanding of melanin production across kingdoms. [Display omitted] •Exophiala dermatitidis can be a model polyextremotolerant and melaninized organism•Its genome-scale model is reconstructed to study melanin and carotenoid metabolism•The shadow price analysis indicates a potential underexplored role of carotenoids•Comparisons between human and E. dermatitidis melanin synthesis are made Microbiology; Bioinformatics; Metabolic Engineering